Olmec lithic economy at San Lorenzo - Hirth, Kenn; Cyphers, Ann (University Press of Colorado e-book collection., 2020)
"Examines specialized production for manufacturing obsidian cutting tools at San Lorenzo, Mexico, the first Olmec center in the southern Gulf Coast as Mesoamerica's earliest complex society between 1800-1000 BC. Through systematic analysis of this commodity and importation of raw material, on-site production, and distribution of finished goods."--Provided by publisher.